Electronic active defects and local order in doped ZnO ceramics inferred from EPR and 27Al NMR investigations. Issue 10 (August 2019) - Sun, Qianying; Tian, Tian; Zheng, Laoying; Man, Zhenyong; Li, Guorong; Barré, Maud; Dittmer, Jens; Bulou, Alain; Kassiba, Abdel Hadi
Abstract: Doped ZnO based ceramics were fabricated by using a solid state reaction of ZnO co-doped by TiO2, Al2 O3 and MgO and sintered in different atmospheres (Air, N2, N2 + CO). The crystalline structures consist in wurtzite ZnO and a minor spinel phase Zn2 TiO4 . The electrical conductivity is modulated by the sintering conditions with the highest value (˜10 5 S m −1 ) obtained in the reducing atmosphere (N2 + CO). The role of defects and vacancies on the electrical behavior was exhaustively investigated by Raman, electron paramagnetic resonance (EPR) and solid state NMR methods. The paramagnetic centres inferred from EPR studies show a Pauli-like spin susceptibility. Their origin was assigned to shallow donors from interstitial defects (Zni ) favored by substitutional Al ions (AlZn ). The NMR spectral features with a characteristic 185 ppm line which correlates with the electrical conductivity are presumed to be caused by the Knight shift effect from the conduction electrons and the involved paramagnetic centres.